2010
DOI: 10.1186/1471-2164-11-360
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses in mouse brain exposed to chronic excess of the neurotransmitter glutamate

Abstract: BackgroundIncreases during aging in extracellular levels of glutamate (Glu), the major excitatory neurotransmitter in the brain, may be linked to chronic neurodegenerative diseases. Little is known about the molecular responses of neurons to chronic, moderate increases in Glu levels. Genome-wide gene expression in brain hippocampus was examined in a unique transgenic (Tg) mouse model that exhibits moderate Glu hyperactivity throughout the lifespan, the neuronal Glutamate dehydrogenase (Glud1) mouse, and litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 101 publications
(117 reference statements)
2
38
0
Order By: Relevance
“…To test our hypothesis that chronic asymptomatic domoic acid exposure in zebrafish produces brain transcriptome-level changes consistent with chronic excess synaptic glutamate release, we compared the gene transcriptome changes in zebrafish with reported gene transcriptome changes in the hippocampi of Glud1 transgenic mice (Wang et al, 2010). This mouse model was developed in order to study the neurological consequences of excess glutamatergic stimulation, and constitutively over-expresses a copy of the glud1 gene, leading to moderate over-production of glutamate and increased (~30%) release of glutamate during synaptic transmission (Bao et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To test our hypothesis that chronic asymptomatic domoic acid exposure in zebrafish produces brain transcriptome-level changes consistent with chronic excess synaptic glutamate release, we compared the gene transcriptome changes in zebrafish with reported gene transcriptome changes in the hippocampi of Glud1 transgenic mice (Wang et al, 2010). This mouse model was developed in order to study the neurological consequences of excess glutamatergic stimulation, and constitutively over-expresses a copy of the glud1 gene, leading to moderate over-production of glutamate and increased (~30%) release of glutamate during synaptic transmission (Bao et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…We compared transcriptome results from the brains of chronically-exposed zebrafish to hippocampi from nine-month old Glud1 mice (Wang et al, 2010), and identified transcriptional changes for genes from two IPA Bio Functions groups in both the present study and the Glud1 mouse study: 1) Nervous System Function & Development ; and 2) Cell Death . However, individual gene transcription responses in zebrafish were different from those reported in the Glud1 mouse hippocampus (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations